2017
DOI: 10.1002/ange.201703264
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent and Ultrastable CsPbBr3 Perovskite Quantum Dots Incorporated into a Silica/Alumina Monolith

Abstract: We successfully prepared QDs incorporated into as ilica/alumina monolith (QDs-SAM) by as imple sol-gel reaction of an Al-Si single precursor with CsPbBr 3 QDs blended in toluene solution, without adding water and catalyst. The resultant transparent monolith exhibits high photoluminescence quantum yields (PLQY) up to 90 %, and good photostability under strong illumination of blue light for 300 h. We show that the preliminary ligand exchange of didodecyl dimethyl ammonium bromide (DDAB) was very important to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(166 citation statements)
references
References 43 publications
2
164
0
Order By: Relevance
“…[50] Figure S1 (Supporting Information) shows S-AIMs with irregular shapes and randomly distributed particle size at 0.5-50 µm, which are www.advmattechnol.de further confirmed by the scanning electron microscopy (SEM) images in Figure 3b. [23,27,51] S-AIMs can effectively solve this issue since the PQD mean size of 22 nm ( Figure S4, Supporting Information) is comparable to the S-AIM mean pore size of 20 nm ( Figure S5, Supporting Information). These random pore structures and the rough surface lead to a combined effect, preventing the ambient moisture from penetrating into the S-AIMs, and as will be discussed in the following, serve for protecting the PQDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] Figure S1 (Supporting Information) shows S-AIMs with irregular shapes and randomly distributed particle size at 0.5-50 µm, which are www.advmattechnol.de further confirmed by the scanning electron microscopy (SEM) images in Figure 3b. [23,27,51] S-AIMs can effectively solve this issue since the PQD mean size of 22 nm ( Figure S4, Supporting Information) is comparable to the S-AIM mean pore size of 20 nm ( Figure S5, Supporting Information). These random pore structures and the rough surface lead to a combined effect, preventing the ambient moisture from penetrating into the S-AIMs, and as will be discussed in the following, serve for protecting the PQDs.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Particularly, PQDs suffer from low chemical and optical stabilities, resulting in their fast degradation under exposure to moisture, heat, and light irradiance. [13,14] Current research efforts therefore aim at enhancing the stability of PQDs by covering them in inorganic materials, including CdS, [15] zeolite, [16,17] glass, [18,19] CaF 2 , [20] Al 2 O 3 , [21][22][23] SiO 2 , [24][25][26][27][28][29] and TiO 2 . [13,14] Current research efforts therefore aim at enhancing the stability of PQDs by covering them in inorganic materials, including CdS, [15] zeolite, [16,17] glass, [18,19] CaF 2 , [20] Al 2 O 3 , [21][22][23] SiO 2 , [24][25][26][27][28][29] and TiO 2 .…”
mentioning
confidence: 99%
“…Copyright 2017, Wiley‐VCH). f) Optical image of QDs‐SAM powder (Reproduced with permission . Copyright 2017, Wiley‐VCH).…”
Section: Stability Of Pqdsmentioning
confidence: 99%
“…These results suggested that a complete replacement of OLA and OA by DDAB was achieved. Similar ligand exchange route was employed by Li's group . They found that the balanced external environment of CsPbBr 3 nanocrystal inks would be disrupted during the SiO 2 /Al 2 O 3 sol–gel process.…”
Section: Surface Engineeringmentioning
confidence: 75%
“…c) Photographs of CsPbBr 3 nanocrystals and DDAB‐treated CsPbBr 3 nanocrystals after adding di‐sec‐butoxyaluminoxytriethoxysilane (DBATES) into solutions and their corresponding monolith with different content of perovskites. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Surface Engineeringmentioning
confidence: 99%